Passively Q-switched mode-locked Ho, Pr:LiLuF4 laser operating at 2.9 µm with semiconductor saturable absorber mirror. (18th October 2018) - Yang, Yaling; Nie, Hongkun; Zhang, Baitao; Yang, Kejian; Zhang, Peixiong; Sun, Xiaoli; Yan, Bingzheng; Li, Guoru; Wang, Yiran; Liu, Junting; Shi, Bingnan; Wang, Ruihua; et al.
Abstract: We demonstrated a passively Q-switched mode-locked 2.9 µm Ho, Pr:LiLuF4 bulk laser based on a semiconductor saturable absorber mirror for the first time, to the best of our knowledge. A stable pulse train with a modulation depth of nearly 100% was obtained. The mode-locked pulse width inside the Q-switched pulse envelope was estimated to be approximately 800 ps with a repetition rate of 47.27 MHz. The maximum average output power was determined to be 146 mW with a Q-switched pulse repetition rate of 18.2 kHz at a center wavelength of 2883 nm.